Identifying financial distress firms: a case study of Malaysia’s Government Linked Companies (GLC) - Mohd. Israil, Khaliq Ahmad; Motawe Altarturi, Basheer Hussein; Thas Thaker, Hassanudin Mohd; Harun, Md Yousuf; Nahar, Nurun (International Journal of Economics, Finance and Management, 2014)
The unhealthy financial state can be a massive and can cause long term distress which can result to restrictions of investments activities, capital flows and performance of firms. Thus it is vital for organizations to identify the reasoning that may lead to a corporate failure and take measures accordingly to refrain from such condition. Thus, this present study addresses the financial distress measurement among 30 GLC’s listed companies in Bursa Malaysia over the period of five years (2008 until 2012). This paper asses the financial distress determinant measured by Z score statistics model. Further on, determinant such as current ratio and debt ratio were identified. Results show that there is significant relationship between both variables and Z – Scores that determine financial distressed of the GLC.